Agile processes in software engineering and extreme programming : workshops : XP 2019 workshops, Montréal, QC, Canada, May 21-25, 2019, proceedings /: workshops : XP 2019 workshops, Montréal, QC, Canada, May 21-25, 2019, proceedings. ([2019]) - Unknown
No abstract available